The great humanist of India (the 100th anniversary of the Nobel Prize) (Journal of Oriental Studies, 2016)
Article is dedicated to the 100th anniversary of the Nobel Prize in Literature to the great Indian poet, writer and educator Rabindranath Tagore. He was the first Asian writer, whose work was rated so highly.
Keywords: India; Guru; «Gitanjali» Shantiniketon